2023
DOI: 10.1186/s12943-022-01683-w
|View full text |Cite
|
Sign up to set email alerts
|

Circulating biosignatures in multiple myeloma and their role in multidrug resistance

Abstract: A major obstacle to chemotherapeutic success in cancer treatment is the development of drug resistance. This occurs when a tumour fails to reduce in size after treatment or when there is clinical relapse after an initial positive response to treatment. A unique and serious type of resistance is multidrug resistance (MDR). MDR causes the simultaneous cross resistance to unrelated drugs used in chemotherapy. MDR can be acquired through genetic alterations following drug exposure, or as discovered by us, through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 129 publications
0
5
0
Order By: Relevance
“…The functional proteins or non‐coding RNAs contained in exosomes secreted by tumour cells mediate drug resistance through the regulation of drug efflux and metabolism 29 . Research suggests that the diversion of EVs from cancer cells contributes to their resistance to chemotherapeutic agents through increased active drug efflux 22,28–46 . Recent pharmacological studies have shown that inhibiting EV release could be a new strategy to make cancer cells more susceptible to anticancer drug treatment 32,37–39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional proteins or non‐coding RNAs contained in exosomes secreted by tumour cells mediate drug resistance through the regulation of drug efflux and metabolism 29 . Research suggests that the diversion of EVs from cancer cells contributes to their resistance to chemotherapeutic agents through increased active drug efflux 22,28–46 . Recent pharmacological studies have shown that inhibiting EV release could be a new strategy to make cancer cells more susceptible to anticancer drug treatment 32,37–39 .…”
Section: Discussionmentioning
confidence: 99%
“… 29 Research suggests that the diversion of EVs from cancer cells contributes to their resistance to chemotherapeutic agents through increased active drug efflux. 22 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 Recent pharmacological studies have shown that inhibiting EV release could be a new strategy to make cancer cells more susceptible to anticancer drug treatment. 32 , 37 , 38 , 39 While significant progress has been made in exosome/sEV research in recent years, no medications that specifically target the inhibition of sEV secretion have been approved for human use.…”
Section: Discussionmentioning
confidence: 99%
“…These vesicles function as transporters of bioactive molecules, such as proteins, lipids, and nucleic acids, enabling communication between cells and impacting the behavior of the cells they interact with. Exosomes derived from BMSCs and myeloma cells are of great significance in the study of MM [ 143 ]. They possess a wide range of signaling molecules, including cytokines, growth factors, and miRNAs, that have the ability to modify the characteristics of myeloma cells and bolster their ability to survive and resist treatment [ 143 ].…”
Section: Bone Marrow: a Specialty That Fosters Growthmentioning
confidence: 99%
“…Exosomes derived from BMSCs and myeloma cells are of great significance in the study of MM [ 143 ]. They possess a wide range of signaling molecules, including cytokines, growth factors, and miRNAs, that have the ability to modify the characteristics of myeloma cells and bolster their ability to survive and resist treatment [ 143 ].…”
Section: Bone Marrow: a Specialty That Fosters Growthmentioning
confidence: 99%
See 1 more Smart Citation